La Creación Musical En El Proceso Cinematográfico. Una Perspectiva Crítica - Dr. José Ángel LÁZARO LÓPEZ, (Fonseca, Journal of Communication, 2023)
This research approaches, from a double perspective, music creation within film creation processes. On the one hand, the academic approach, truly scarce in relation to creative processes, exhibits a historical stagnation onto a series of platitudes which the newest research initiatives have failed to overcome. These initiatives, coming from areas such as musicology, cultural studies or philosophy, end up standing on the margins of the proper area of film theory.